Zirconium oxide graphene composite ceramic membrane as well as preparation method and application thereof
By introducing graphene powder and optimizing structure into the ceramic membrane, the problems of high brittleness, easy pollution and low flux of ceramic membrane are solved, the mechanical strength and pollution resistance are improved, high throughput and selective separation are achieved, and the expansion is achieved. The scope of application is reduced and production costs are reduced.
Patent Information
- Application Number
- CN202411560220.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional ceramic membranes have problems such as high brittleness, easy contamination and low flux, which limit their performance and range in processing, use and application.
Using zirconia graphene composite ceramic membrane, a high-strength, high-modulus and flexible zirconia graphene support framework is formed by introducing graphene powder, combining porous base layer and selective filter layer to optimize porosity structure and porosity. , improve mechanical strength, pollution resistance and separation efficiency.
It significantly improves the mechanical strength and toughness of the ceramic membrane, extends the service life, reduces the risk of contaminants adhesion, maintains high throughput, achieves good selective separation, broadens the scope of application, and reduces production costs.
Smart Images

Figure CN119139937A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite membrane materials, and in particular to a zirconia graphene composite ceramic membrane and a preparation method and application thereof. Background Art
[0002] Membrane separation technology, as a cutting-edge and efficient separation method, has shown great potential in the fields of material separation, purification and concentration by virtue of its membrane's selective separation characteristics. With the rapid advancement of industrial technology, the demand for efficient and environmentally friendly separation technology has become increasingly urgent. In this context, ceramic membranes have stood out with their unique performance advantages and have become a bright new star in the field of membrane materials, heralding a broad development prospect.
[0003] The core advantage of ceramic membranes lies in their excellent separation efficiency and stability. They can accurately separate and purify different components in the feed liquid, while showing strong resistance to acids, alkalis and organic solvents, ensuring stable operation in extreme chemical environments. This feature makes ceramic membranes widely used in many key fields such as food and beverage processing, deep processing of plants (drugs), biomedicine, fermentation industry and fine chemicals. Specifically, in the food industry, it helps to purify products such as fruit juice, alcohol, and milk powder; in the pharmaceutical field, it has become an important tool for the separation and purification of biological products; and in water treatment, ceramic membranes have made an indelible contribution and are widely used in key links such as water purification, wastewater treatment and seawater desalination.
[0004] However, ceramic membranes are not perfect. Although their high hardness and wear resistance are advantages, they are also relatively brittle, making them easily damaged during processing, installation and use. In addition, during long-term use, pollutants tend to accumulate on the membrane surface, affecting the flux and reducing the separation efficiency. Furthermore, although ceramic membranes have high-precision separation capabilities, their permeability is relatively limited, which poses a certain limitation in application scenarios that require high-flow processing. Summary of the invention
[0005] In order to solve the above-mentioned problems, the present application provides a zirconia graphene composite ceramic membrane and its preparation method and application, aiming to overcome the limitations of traditional ceramic membranes such as high brittleness, easy contamination and low flux, and further improve its performance and application scope.
[0006] In the first aspect, the present application provides a zirconium oxide graphene composite ceramic membrane adopts the following technical solution: A zirconia graphene composite ceramic membrane comprises a porous substrate layer, a zirconia graphene support skeleton, and a selective filtration layer arranged in sequence. The raw materials for preparing the zirconia graphene support skeleton comprise the following components in parts by weight: 35-40 parts of zirconia powder, 12-16 parts of graphene powder, 1-3 parts of sintering aid, 1-4 parts of pore former, and 0.8-1.2 parts of adhesive.
[0007] By adopting the above technical solution: introducing graphene powder into the zirconia ceramic matrix, utilizing the high strength, high modulus and excellent flexibility of graphene, the mechanical strength and toughness of the composite ceramic membrane are significantly improved, effectively overcoming the problem of high brittleness of traditional ceramic membranes, and the two-dimensional layered structure of graphene forms a good network structure in the ceramic matrix, enhancing the overall mechanical properties of the material; In addition, graphene has excellent chemical stability and anti-fouling properties, and its surface energy is low, so it is not easily adsorbed by pollutants. Therefore, introducing graphene into zirconia ceramic membranes can effectively improve the membrane's anti-fouling ability, extend the membrane's service life, and reduce the frequency of cleaning and maintenance. The synergistic effect of the porous substrate layer and the selective filtration layer, combined with the excellent performance of the zirconia graphene support skeleton, enables the composite ceramic membrane to achieve good selective separation while maintaining high flux. This is of great significance for improving production efficiency and reducing energy consumption.
[0008] Preferably, the raw materials for preparing the zirconia graphene support skeleton include the following components in parts by weight: 36 parts of zirconia powder, 14 parts of graphene powder, 2.5 parts of sintering aid, 2 parts of pore former, and 1.2 parts of adhesive.
[0009] By adopting the above technical solution: optimizing the ratio of raw materials for preparing the supporting skeleton, the prepared zirconia graphene supporting skeleton can further improve the performance of the composite ceramic membrane.
[0010] Preferably, the porous substrate layer is composed of a composite of zirconium oxide and aluminum oxide, wherein the pore size of the porous substrate layer is 20-60 μm and the porosity is 15-30%.
[0011] By adopting the above technical solution: the porous base layer is composed of a composite of zirconium oxide and aluminum oxide, both of which have high melting points, high strength and good chemical stability, and can therefore provide solid mechanical support for the entire ceramic membrane, which helps reduce the possibility of deformation or rupture of the membrane during use and extend its service life.
[0012] In addition, the pore size of the porous substrate layer is controlled within the range of 20-60 μm. This size range is conducive to the formation of a uniform microporous structure, thereby enhancing the permeability and selectivity of the membrane. At the same time, the porosity is controlled between 15-30%, which not only ensures sufficient flux but also avoids the decrease in mechanical strength caused by excessively high porosity.
[0013] The fine pore structure of the porous substrate layer can form a good synergistic effect with the zirconia graphene support skeleton and the selective filtration layer, thereby improving the separation efficiency of the membrane, making it more effective in intercepting impurities and separating components when processing complex fluids, and not easily adsorbed by pollutants. At the same time, the uniform pore structure also reduces the risk of pollutants depositing and clogging on the membrane surface.
[0014] Preferably, the material of the selective filtration layer may be one or more of polyvinylidene fluoride, polyethersulfone, graphene oxide, titanium dioxide, zeolite, and aluminum oxide.
[0015] By adopting the above technical solution: the application scope of zirconia graphene composite ceramic membrane can be further broadened.
[0016] Preferably, the pore size of the zirconia graphene support skeleton is 1.5-5 μm, and the porosity is 40-55%.
[0017] By adopting the above technical solution: larger pore size and moderate porosity make the supporting skeleton have a higher flux, which means that under the same operating conditions, the composite ceramic membrane can process more fluid and improve the processing efficiency, which is particularly important for large-scale industrial applications and can significantly reduce production costs.
[0018] Preferably, the sintering aid is selected from at least one of yttrium oxide, such as lanthanum oxide, and cerium oxide; the pore-forming agent is selected from at least one of carbon powder, starch, and polymethyl methacrylate; and the adhesive is selected from at least one of methyl cellulose and polyvinyl alcohol.
[0019] By adopting the above technical scheme: preferably selecting sintering aids, pore formers and adhesives, it is possible to achieve fine control of the preparation process of zirconia graphene composite ceramic membranes, thereby optimizing their pore structure, improving mechanical strength, and improving permeability and selectivity.
[0020] In a second aspect, the present application provides a method for preparing a zirconium oxide graphene composite ceramic film, which adopts the following technical scheme: A method for preparing a zirconia graphene composite ceramic membrane comprises the following steps: a. preparing zirconia powder, graphene powder, a sintering aid, a pore former and an adhesive, mixing them according to a predetermined amount of materials, grinding them evenly, pressing them into embryos, drying them for 1-2 hours, mixing raw materials for preparing a porous substrate layer to form a slurry, coating the slurry on the embryos, and calcining them at 1200-1350° C. to obtain a prefabricated precursor; b. preparing a selective filtration layer on the prefabricated precursor obtained in a, and obtaining the zirconia graphene composite ceramic membrane after drying.
[0021] By adopting the above technical solution: zirconium oxide, graphene, porous substrate layer material and selective filtration layer material can be successfully combined together to form a composite ceramic membrane with excellent performance.
[0022] In the third aspect, the present application provides an application of a zirconia graphene composite ceramic membrane, which adopts the following technical solution: application of zirconia graphene composite ceramic membrane in seawater filtration, reverse osmosis, and sewage treatment.
[0023] In summary, the present application includes at least one of the following beneficial effects: 1. The present application overcomes the limitations of traditional ceramic membranes, such as high brittleness and easy contamination, by introducing graphene powder into a zirconia ceramic matrix to prepare a supporting skeleton. The high strength, high modulus and excellent flexibility of graphene significantly improve the mechanical strength and toughness of the composite ceramic membrane, which not only enhances the durability of the membrane, but also reduces the risk of rupture under complex working conditions. At the same time, its chemical stability and low surface energy characteristics effectively improve the anti-pollution ability of the membrane, extend its service life and reduce maintenance costs. In addition, by optimizing the pore structure and porosity of the porous substrate layer and the zirconia graphene supporting skeleton, and selecting appropriate selective filtration layer materials, the composite ceramic membrane can achieve good selective separation while maintaining high flux; 2. This application can further broaden the application scope of the zirconia graphene composite ceramic membrane by flexibly selecting the material of the selective filtration layer, meet the needs of different fields for high-performance ceramic membranes, and the preparation method has clear steps, is easy to realize industrial production, accurately controls the raw material ratio and preparation process, and realizes fine regulation of the performance of the composite ceramic membrane, ensuring stable and reliable product quality; 3. The zirconia graphene composite ceramic membrane in this application performs well in applications in environmental protection fields such as seawater filtration, reverse osmosis, and sewage treatment. Its efficient filtration and capture performance brings significant economic benefits, reduces production costs, and improves resource utilization efficiency.
[0024] Reference numerals Figure 1 This is an electron microscope image of the zirconium oxide graphene support skeleton of Example 11 of the present application; Figure 2 This is a 1000X electron microscope image of the zirconium oxide graphene composite ceramic membrane of Example 11 of the present application; Figure 3 This is a 6000X electron microscope image of the zirconium oxide graphene composite ceramic membrane of Example 11 of the present application. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials. raw material Specifications / Manufacturer Polyvinylidene fluoride KF Polymer PVDF Polyethersulfone Guangdong Youju New Materials Polyvinyl alcohol Wanwei Group Wanwei PVA 26-99(L)
[0026] Performance testing and analysis 1. Brittleness: According to GB4742-B4 standard, the impact resistance is tested, and the impact toughness index (ak The actual significance of ak value is to reveal the tendency of the material to become brittle, which reflects the resistance of the metal material to external impact loads. Generally speaking, a high ak value is considered to be tough, while a low ak value is called brittle. 1. Flux: Refer to GB / T 43300-2023 Ceramic Flat Membrane Pure Water Flux Test Method for pure water flux test, and C1 represents pure water flux; 2. Anti-oil pollution: Make your own oil-water emulsion, filter the oil-water emulsion with the prepared zirconia graphene composite ceramic membrane for 2 hours, and then filter it with pure water again for 0.5 hours, and test the pure water flux, which is represented by C2.
[0027] Example 1 A zirconium oxide graphene composite ceramic membrane is composed of a porous substrate layer, a zirconium oxide graphene support skeleton, and a selective filtration layer arranged in sequence, wherein the porous substrate layer is composited with zirconium oxide and aluminum oxide, and the material used for the selective filtration layer is composed of polyvinylidene fluoride and polyether sulfone. The specific preparation method is as follows: 1. Prepare 6g zirconium oxide powder and 4g alumina powder, mix them and grind them in a ball mill for 20 minutes until they are uniform, add 0.1g activated carbon powder, 25g isopropanol and 10g water to make a slurry for standby use; 2. Prepare zirconium oxide powder, graphene powder, sintering aid, pore former and adhesive, mix and grind them with a ball mill for 45 minutes until they are uniform, then press them into embryos at a pressure of 20MPa, dry the embryos at 40°C for 2 hours, then spray the slurry obtained in a on one side of the embryos with a spray gun, and then place them in a tubular furnace for calcination at 1200-1350°C for 4 hours, take them out of the furnace, and cool them to obtain a prefabricated precursor; 3. Prepare 2g of polyvinylidene fluoride and 3.2g of polyethersulfone, add 5ml of DMF-NMP mixed solvent, wherein the volume ratio of DMF / NMP in the DMF-NMP mixed solvent is 70%:30%, stir at 64°C for 50min until fully dissolved to form a transparent or translucent sol; immerse the prefabricated precursor in the sol, keep it for 20min and then take it out to make the sol evenly adhere to the surface of the membrane, remove the excess sol, place it in an oven at 80°C and dry it for 2d, condense and solidify it, and obtain the zirconium oxide graphene composite ceramic membrane in this application; The porous substrate layer has a pore size of 20-30 μm, a porosity of 27%, and a thickness of 10 μm; the pore size of the zirconium oxide graphene support skeleton is 3-5 μm, a porosity of 42%, and a thickness of 8 μm; the thickness of the selective filtration layer is 20 nm; the sintering aid is lanthanum oxide, the pore-forming agent is corn starch, and the adhesive is selected from polyvinyl alcohol.
[0028] Table: Raw materials and contents of zirconium oxide graphene support skeleton in Example 1 Preparation of raw materials Content (g) Zirconia powder 3.5 Graphene powder 1.2 Sintering Aids 0.1 Pore forming agent 0.1 Adhesive 0.08 Example 2-11 A zirconia graphene composite ceramic membrane, the preparation method and raw materials used are consistent with those in Example 1, the only difference is that the amounts of raw materials used in the preparation are different, as shown in the table below.
[0029] Table: Raw materials and contents of zirconium oxide graphene support skeletons prepared in Examples 2-11 The performance of the zirconia graphene composite ceramic membranes prepared in Examples 1-11 was tested according to the aforementioned test standards, and the test results are shown in the table below.
[0030] It can be seen from the above table that the zirconia graphene composite ceramic membranes prepared by Examples 1-11 show excellent impact resistance. At the same time, their fluxes all show high values, and the flux after contamination does not show a significant decrease, which indicates that the zirconia graphene composite ceramic membrane overcomes the limitations of traditional ceramic membranes such as high brittleness, easy contamination and low flux.
[0031] Analyze the possible reasons: The combination of zirconium oxide and graphene significantly improves the mechanical strength of the ceramic membrane, including tensile strength, compressive strength and toughness, which enables the composite ceramic membrane to better resist cracking and damage when facing impact loads, thereby extending the service life of the membrane. The introduction of graphene not only enhances the mechanical properties of the membrane, but also uses its low surface energy characteristics and chemical stability to resist the attachment of pollutants. This characteristic enables the composite ceramic membrane to maintain a high flux during long-term operation, reducing performance degradation and cleaning frequency caused by pollution; In addition, by optimizing the pore structure and porosity of the porous substrate layer and the zirconia graphene supporting skeleton, and selecting appropriate selective filtration layer materials, the composite ceramic membrane can achieve good selective separation while maintaining high flux. This high flux characteristic makes the composite ceramic membrane have broad application prospects in a variety of separation and filtration applications.
[0032] Example 12 A zirconium oxide graphene composite ceramic membrane is composed of a porous substrate layer, a zirconium oxide graphene support skeleton, and a selective filtration layer arranged in sequence, wherein the porous substrate layer is composited with zirconium oxide and aluminum oxide, and the material used for the selective filtration layer is composed of zeolite. The specific preparation method is as follows: a. Prepare 6g zirconium oxide powder and 4g alumina powder, mix them and grind them with a ball mill for 20 minutes until they are uniform, add 0.1g activated carbon powder, 25g isopropanol and 10g water to make a slurry for standby use; b. Prepare zirconium oxide powder, graphene powder, sintering aid, pore former and adhesive, mix and grind them with a ball mill for 45 minutes until they are uniform, then press them into embryos at a pressure of 20MPa, dry the embryos at 40°C for 2 hours, then spray the slurry obtained in a on one side of the embryos with a spray gun, and then place them in a tubular furnace for calcination at 1200-1350°C for 4 hours, take them out of the furnace, and cool them to obtain a prefabricated precursor; c. Prepare 8g of zeolite, grind it into powder with an average particle size of less than 20μm in a ball mill, add 1.43g of polyacrylic acid and 10ml of acetone to form a suspension, spray the suspension on the surface of the preform, place it in an oven at 60°C and dry it for 1d, condense and solidify it, and obtain the zirconium oxide graphene composite ceramic membrane in this application; The porous substrate layer has a pore size of 20-30 μm, a porosity of 27%, and a thickness of 10 μm; the pore size of the zirconium oxide graphene support skeleton is 3-5 μm, a porosity of 42%, and a thickness of 8 μm; the thickness of the selective filtration layer is 20 nm; the sintering aid is lanthanum oxide, the pore-forming agent is corn starch, and the adhesive is selected from polyvinyl alcohol.
[0033] Comparative Example 1 A composite ceramic membrane, the preparation method of which is the same as that of Example 1, the only difference being that an equal amount of alumina powder is used to replace zirconium oxide powder in the preparation raw material of the zirconium oxide graphene support skeleton.
[0034] Comparative Example 2 A composite ceramic membrane, the preparation method of which is the same as that of Example 1, the only difference being that an equal amount of graphene oxide powder is used to replace graphene powder in the preparation raw material of the zirconium oxide graphene support skeleton.
[0035] Embodiment 13 A zirconia graphene composite ceramic membrane consists of a porous base layer, a zirconia graphene support skeleton, and a selective filtration layer arranged in sequence, wherein the porous base layer is composited with zirconium oxide and aluminum oxide, and the selective filtration layer is made of polyvinylidene fluoride and polyether sulfone. The only difference is that the pore size of the porous base layer is 3-5μm, and the porosity is 27%; the pore size of the zirconia graphene support skeleton is 20-30μm, and the porosity is 42%.
[0036] Embodiment 14 A zirconia graphene composite ceramic membrane consists of a porous base layer, a zirconia graphene support skeleton, and a selective filtration layer arranged in sequence, wherein the porous base layer is composited with zirconium oxide and aluminum oxide, and the selective filtration layer is made of polyvinylidene fluoride and polyether sulfone. The only difference is that the pore size of the porous base layer is 3-5μm, and the porosity is 42%; the pore size of the zirconia graphene support skeleton is 20-30μm, and the porosity is 27%.
[0037] The performance of the zirconia graphene composite ceramic membranes prepared in Examples 12-14 and Comparative Examples 1-2 was tested according to the aforementioned test standards. The test results are shown in the table below.
[0038] It can be seen from the above table that the zirconia graphene composite ceramic membranes prepared by Examples 12-14 and Comparative Examples 1-2 show different differences in impact toughness, flux C1, and flux C2, among which the various properties in Example 12 fluctuate slightly, but the overall performance is still excellent; The impact toughness of Comparative Examples 1 and 2 decreased significantly compared with Example 1, and the flux C2 also decreased to a certain extent after pollution, which indicates that they have defects such as insufficient anti-fouling ability and high brittleness; As for Examples 13 and 14, their impact toughness did not show a significant change, and a more obvious decrease occurred in flux C1 and flux C2 after pollution, which indicates that they have defects of low flux and poor anti-fouling ability.
[0039] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. A zirconium oxide graphene composite ceramic membrane, characterized in that: It comprises a porous substrate layer, a zirconia graphene support skeleton, and a selective filtering layer arranged in sequence, and the raw materials for preparing the zirconia graphene support skeleton include the following components in parts by weight: 35-40 parts of zirconium oxide powder Graphene powder 12-16 parts Sintering aid 1-3 parts Pore forming agent 1-4 parts Adhesive 0.8-1.2 parts.
2. The zirconium oxide graphene composite ceramic membrane according to claim 1, characterized in that: The raw materials for preparing the zirconia graphene support skeleton include the following components in parts by weight: Zirconia powder 36 parts Graphene powder 14 parts 2.5 parts of sintering aid 2 parts of pore forming agent 1.2 parts of adhesive.
3. The zirconium oxide graphene composite ceramic membrane according to claim 1, characterized in that: The porous substrate layer is composited by zirconium oxide and aluminum oxide, wherein the pore size of the porous substrate layer is 20-60 μm and the porosity is 15-30%.
4. The zirconium oxide graphene composite ceramic membrane according to claim 1, characterized in that: The material of the selective filtering layer may be one or more of polyvinylidene fluoride, polyethersulfone, graphene oxide, titanium dioxide, zeolite, and aluminum oxide.
5. The zirconium oxide graphene composite ceramic membrane according to claim 1, characterized in that: The pore size of the zirconium oxide graphene support skeleton is 1.5-5 μm, and the porosity is 40-55%.
6. The zirconium oxide graphene composite ceramic membrane according to claim 1, characterized in that: The sintering aid is selected from at least one of yttrium oxide, such as lanthanum oxide, and cerium oxide; the pore-forming agent is selected from at least one of carbon powder, starch, and polymethyl methacrylate; and the adhesive is selected from at least one of methyl cellulose and polyvinyl alcohol.
7. A method for preparing a zirconium oxide graphene composite ceramic membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: a. Prepare zirconium oxide powder, graphene powder, sintering aid, pore former and adhesive, mix them according to the predetermined amount, grind them evenly, and then press them into embryos. After drying for 1-2 hours, mix the raw materials for preparing the porous substrate layer to make a slurry, apply it on the embryos, and calcine them at 1200-1350°C to obtain a prefabricated precursor; b. Prepare a selective filtration layer on the prefabricated precursor obtained in a, and obtain the zirconium oxide graphene composite ceramic membrane after drying.
8. Application of the zirconium oxide graphene composite ceramic membrane according to any one of claims 1 to 6 in seawater filtration, reverse osmosis and sewage treatment.
